Legal Problems Relating to the Advertising of Private Healthcare Facilities - Raisiri, Naipapon; Potjananurat, Orawan; Thongraweewong, Kanathip (Mahachula Academic Journal, 2026)
This research article aims to: 1) study the legal problems and obstacles in enforcing the Sanatorium Act, B.E. 2541 (1998) and its amendments, concerning the advertising control of private healthcare facilities, particularly beauty clinics; 2) comparatively analyze the legal problems related to advertising control against the laws of the Republic of Korea and the Commonwealth of Australia; and 3) propose guidelines for effective legal amendments. This qualitative research is based on a documentary study. The research framework utilizes the analysis of legal provisions and the economic analysis of law theory, with the qualitative data analyzed using a descriptive approach. Findings were as follows: 1) The legal problems and obstacles in enforcing the Sanatorium Act, B.E. 2541consist of four main issues: repeated offenses, the authority of competent officials under Section 46, the penalty provisions under Section 68, and the composition of the Case Settlement Committee under Section 75. 2) The comparative legal analysis indicates that Thailand's laws still have limitations in addressing digital media, and the penalty rates do not align with the principle of proportionality when compared to other countries. 3) The proposed guidelines for effective legal amendments include: amending Section 68 to grant the authority to suspend licenses and increase the maximum fine to 100,000 baht; amending Section 46 to empower competent officials to inspect and suspend advertisements on computer systems; and amending Section 75 to allow the Chairman of the Case Settlement Committee to delegate their authority to others.